Toward a unified theory of development connectionism and dynamic systems theory re-considered - Spencer, John P.; Thomas, Michael S. C.; McClelland, James L. (New York ; Oxford : Oxford University Press, 2009)
This resource defines and refines two major theoretical approaches within developmental science that address the central issues of development-connectionism and dynamical systems theory.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Developmental psychology; Cognitive psychology; Connectionism; Differentiable dynamical systems; Dynamics